2022
DOI: 10.1051/bioconf/20224501004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the qualitative parameters of raw sheep’s milk with the potential for the production of traditional artisanal cheese

Abstract: The aim of the present study was to investigate the physicochemical and microbiological profile of indigenous sheep’s milk with the potential for the production of artisanal cheese. The data showed the changes in lactation stages (between April and August) up to 2 hours following manual milk production. The quality of raw milk in the production of brined cheese using traditional technology was assessed. The amount of dry matter was21.36% in April and 19.85% in August at the end of lactation. The fat content fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
2
4
1
Order By: Relevance
“…Our study's amino acid composition profiles were similar to those reported previously by other authors, causing quantitative and qualitative differences [9,23,24].…”
Section: Results and Duscussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study's amino acid composition profiles were similar to those reported previously by other authors, causing quantitative and qualitative differences [9,23,24].…”
Section: Results and Duscussionsupporting
confidence: 90%
“…Traditional artisan cheeses acquire a specific milkysour taste during ripening, which cannot yet be related to the activity of certain strain cultures. Isolation of some representatives of the species L. plantarum and L. delbrueckii, as well as other species of lactic acid bacteria, is quantitatively and qualitatively inconsistent, related to different environmental conditions [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The fat content decreased in the middle of the lactation period, with a slight increase being observed toward the end. These variations were probably due to the change in composition of the meadows and the metabolic adaptations of the sheep to changes in the climatic, physiological, and nutritional conditions specific to the milking period [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sheep’s milk and dairy products derived from it have been an integral part of human nutrition for several centuries; their use in human nutrition is mainly due to the essential constituents: micro- and macronutrients (fatty acids, vitamins, trace elements, etc.) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation